Abordagem dietética para parar a hipertensão (DASH) e reduzir níveis pressóricos: resultados longitudinais da coorte ELSA-BRASIL - Soraia Menezes Gontijo (2022)
According to the World Health Organization (WHO) approximately 600 million people have systemic arterial hypertension (SAH), estimating a 60% increase in cases by 2025, causing about 7.1 million deaths. In Brazil, SAH affects approximately 38.1 million adult individuals, 60% of whom are elderly, being directly or indirectly responsible for 50% of deaths from cardiovascular diseases (CVD), representing a very high social cost. The etiology of SAH is complex, involving a combination of genetic, biological, environmental and psychosocial factors. The main risk behaviors associated with high blood pressure are: smoking, alcohol, physical inactivity, poor diet and obesity. In 2004, the Brazilian Cardiology and Arterial Hypertension Societies started to recommend in their guidelines the adoption of the Dietary Approaches to Stop Hypertension (DASH) diet in the non-pharmacological treatment of SAH. The DASH diet emphasizes consumption of low-fat fruits, vegetables, and dairy, as well as whole grains, legumes, nuts, fish, and poultry. It also encourages the reduction of the intake of fats, red meat, sweets and sugars. Evidence from experimental studies shows that this dietary pattern contributes to the prevention and control of SAH, promoting the consumption of foods that are sources of nutrients related to the reduction of blood pressure (BP) such as calcium, potassium, magnesium, fiber and unsaturated fatty acids. However, few longitudinal observational studies have investigated the relationship between the DASH diet and blood pressure control, especially in low- and middle-income countries. In view of the above, the present study aims to investigate whether adherence to the DASH diet is related to blood pressure control in about 4 and 8 years of follow-up of the ELSA-Brasil Adult Health Longitudinal Study. Subjects with high blood pressure and who had dietary information at the 1st study visit in 2008-2010 were eligible. Adherence to DASH at the 1st visit was assessed by the food frequency questionnaire (FFQ) and categorized as low, medium and high. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) for building the blood pressure control trajectory were measured at the 3 study visits (2008-10, 2012-14 and 2017-19). Blood pressure control at each visit was defined as the simultaneous occurrence of SBP < 140 mmHg and DBP < 90 mmHg. The resulting control trajectory was categorized according to the frequency of blood pressure control observed in the visits. For the trajectory between visits 1 and 2, three categories were created: a) lack of blood pressure control (reference); b) blood pressure control in 1 visit; c) blood pressure control in 2 visits. For the trajectory in visits 1, 2 and 3, four categories were obtained: a) lack of blood pressure control (reference); b) blood pressure control in 1 visit; c) blood pressure control in 2 visits; d) blood pressure control in 3 visits. Confounding factors (age; gender; education level; smoking; consumption of alcoholic beverages and level of physical activity, total energy consumed; body mass index; cardiovascular disease and diabetes) were measured at the 1st visit. Multinomial logistic regression models were used, having as reference “absence of pressure control”. The average age of the participants was 56.5 years, 53.4% were female. When compared to individuals with low adherence to the DASH diet, individuals with medium and high adherence to the DASH diet at the 1st visit had lower means of both systolic pressure (-3.4 mmHg and -3.6 mmHg, respectively) and diastolic pressure ( -2.2 mmHg and -4.0 mmHg, respectively). Participants with medium and high adherence to the DASH diet also had higher prevalence of blood pressure control at the 1st and 2nd visit (59.4% and 60.2%, respectively). After adjusting for covariates, the results showed that individuals with high (OR= 1.87; 95% CI: 1.19-2.95) and mean (OR=1.56; 95% CI: 1.18-2.06) ) adherence to the DASH diet showed greater chances of blood pressure control in visits 1 and 2, when compared to low adherence. When the three visits were considered, the chances of blood pressure control on the three occasions were 53% (95%CI: 1.03 - 2.27) and 75% (95%CI:0.95 - 3.23) higher for the participants, with medium and high, respectively, adherence than those with low adherence. Our results confirm that hypertensive individuals with greater adherence to the DASH diet showed a better trajectory of blood pressure control, throughout the follow-up, than those with low adherence to DASH. Our results reinforce the importance of public policies to promote healthy eating, with a focus on the DASH diet, as an aid in the treatment of SAH and in the prevention of associated chronic diseases.